The Contextual Teaching and Learning Model Assisted by Word Card Media to Improve Early Reading Skills of Grade 2 Students at SD Negeri 18 Vega, Selimbau District - Dian Sartika (Graduate Program Magister Manajemen Pendidikan, 2026)
This research was conducted to investigate the effectiveness of the Contextual Teaching and Learning (CTL) approach supported by word card media in enhancing the beginning reading abilities of second-grade students at SD Negeri 18 Vega, Selimbau District. A quantitative methodology was adopted, utilizing a pre-experimental design with a one-group pretest–posttest framework. The participants comprised 17 second-grade students, all of whom were included in the study through a saturated sampling technique. Data were gathered through reading tests, classroom observations, and documentation. The validity of the research instrument was evaluated using the Pearson Product Moment correlation, while reliability was measured through Cronbach’s Alpha coefficient. Data analysis involved both descriptive and inferential statistics, including a paired-samples t-test performed using IBM SPSS Statistics 27. The findings demonstrated that all test items satisfied the required validity standards, although the reliability values did not fully reach the generally recommended level. The descriptive analysis indicated an increase in the average score from 57.64 in the pretest to 78.82 in the posttest. Furthermore, the paired-samples t-test revealed a significant difference between students’ scores before and after the intervention (Sig. = 0.000 < 0.05), accompanied by a large effect size (Cohen’s d = 0.85). These results suggest that the application of the CTL model in combination with word card media contributed positively to the improvement of students’ early reading performance. Consequently, the study offers initial empirical support for the use of CTL and word card media as an instructional strategy to foster beginning reading skills in elementary school learners.